2018
DOI: 10.30773/pi.2017.09.20
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Delusion of Theft and Cognitive Functions in Patients with Mild Alzheimer’s Disease

Abstract: Although delusion of theft (DT) is the most frequent type of delusion in Alzheimer’s disease (AD), its relationship to cognitive functions remains unclear. The aim of this study was to demonstrate the relationship between DT and cognitive functions in mild AD. Two hundred eighty-nine mild AD patients were enrolled in this study. These subjects were classified into three groups: patients with no delusions (ND, n=82), patients with paranoid delusions (PD, n=114) and patients with DT (n=93). Cognitive functions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…The mean rank of WMH in the non-delusional group was smaller than that in the delusional group. This suggests that WMH in the left occipital lobe may be related to the occurrence of delusional symptoms, which is partially consistent with the research results of Na HR et al [15] , it is suggest that occipital white matter changes may promotethe occurrence of delusional symptoms in AD patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The mean rank of WMH in the non-delusional group was smaller than that in the delusional group. This suggests that WMH in the left occipital lobe may be related to the occurrence of delusional symptoms, which is partially consistent with the research results of Na HR et al [15] , it is suggest that occipital white matter changes may promotethe occurrence of delusional symptoms in AD patients.…”
Section: Discussionsupporting
confidence: 90%
“…Almost all patients with AD will develop neuropsychiatric symptoms (NPSs) [2] .Studies have found a prevalence of NPS in dementia between 50% and 80% [3] .They have been found to occur before cognitive decline [4] .Some studies have suggested that speci c NPS may be useful as early predictors of AD or dementia [5] .NPSs refers to non-cognitive mental and behavioral symptoms, which involve perception, emotion, behavior and other elds, mainly including hallucinations, delusions, depression, apathy and other symptoms [6] .Studies suggest that NPS may worsen cognitive symptoms and functional decline and have associated these symptoms with accelerated mortality [7] .Moreover, NPS can be di cult to treat [8] .While psychotropic drugs may temporarily alleviate certain NPS, some have severe and harmful effects [9,10] .Patients with dementia often report multiple NPS, and apathy, depression and anxiety are frequently found to be the most commonly reported symptoms in these patients [11,12] .Delusional symptoms are one of the highest burdens that cause pain to caregivers [13] .It is associated with greater functional impairment, malnutrition, increased risk of bedsores, and higher risk of death [11,14] .Previous studies have shown that AD patients with delusional symptoms have faster cognitive decline and more signi cant changes in language and executive function than patients without delusional symptoms [8] .Delusional symptoms in AD patients involves structural and functional changes in the brain. Studies have found that in addition to gray matter changes, white matter changes are also designed in these person, and parietal and occipital white matter changes have been shown to contribute to the development of delusional misjudgment in AD patients [15] .Several neurobiologically related factors may interact with the development of delusional disorders.For example, subcortical integrity is decreased, mainly manifested by chronic small vessel ischemia and lacunar infarction [16] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, as shown in Table 4, all seven patients in both groups with delusion of theft scored lower than 10 on the WMS-R LM II, and all five patients in both groups with scores higher than 10 in the task did not show delusions related to theft. Although AD frequently accompanies delusions of theft (Ropacki and Jeste, 2005), patients with probable AD dementia and delusions of theft show more severe episodic memory impairment than those without similar delusions (Na et al ., 2018). Therefore, our results indicate that delusions of theft in VLOSLP may be associated with episodic memory impairment with or without AD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that WMH observed on MRI of patients with AD is associated with delusions and depression [24]. WMH of the parietal and occipital lobes may impact delusional symptoms in AD patients [25,26].…”
Section: Introductionmentioning
confidence: 99%